Heavy metal distribution in organic and siliceous marine sponge tissues measured by square wave anodic stripping voltammetry. Issue 1 (15th October 2016) - Illuminati, S.; Annibaldi, A.; Truzzi, C.; Scarponi, G.
Abstract: May sponge spicules represent a "tank" to accumulate heavy metals? In this study we test this hypothesis determining the distribution of Cd, Pb and Cu concentrations between organic and siliceous tissues in Antarctic Demospongia ( Sphaerotylus antarcticus, Kirkpatrikia coulmani and Haliclona sp.) and in the Mediterranean species Petrosia ficiformis . Results show that although, in these sponges, spicules represent about 80% of the mass content, the accumulation of pollutant is lower in the spicules than in the corresponding organic fraction. The contribution of tissues to the total sponge content of Cd, Pb and Cu is respectively 99%, 82% and 97% for Antarctic sponges and 96%, 95% and 96% for P. ficiformis, similar in polar and temperate organisms. These results pave the way to a better understanding of the role of marine sponges in uptaking heavy metals and to their possible use as monitor of marine ecosystems, recommend by the Water Framework Directive. Highlights: First data of metal distribution in tissues of Antarctic and Mediterranean sponges Cd Pb and Cu higher concentrations in organic than siliceous tissues Similar bioaccumulation ability in polar and temperate organisms Use of marine sponges as monitors of marine ecosystem in line with WFD